Technology Acceptance, Trust, and Perceived Risk Influencing Consumers’ Purchase Intention for Luxury Brands on Mobile Applications - Chanamai, Rasika; Sasithanakornkaew, Saranthorn; Apisuphachok, Warapan (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aims to examine the influence of technology acceptance factors, namely perceived usefulness and perceived ease of use, together with trust and perceived risk, on consumers’ purchase intention for luxury brands through mobile applications. The study addresses a research gap in the limited integration of the Technology Acceptance Model (TAM), trust, and perceived risk within the context of luxury consumption in mobile application environments, particularly among Thai consumers. A quantitative research design was employed. The sample consisted of 400 consumers aged 25 years and above who had prior experience purchasing luxury brands via mobile applications. Data were collected using a structured questionnaire with a five-point Likert scale. Pearson’s correlation analysis was conducted to examine the relationships between variables, followed by multiple regression analysis to test the combined influence of independent variables on purchase intention. The results revealed that perceived usefulness, perceived ease of use, trust, and perceived risk were all significantly correlated with purchase intention. However, when analyzed simultaneously using multiple regression, perceived risk was the only significant predictor of purchase intention, whereas the other variables did not show statistically significant effects. This finding suggests that, in the context of luxury products where transaction value and uncertainty are high, consumers place greater emphasis on risk evaluation than on technological convenience or perceived benefits. The study contributes to the literature by extending the application of TAM through the integration of perceived risk in high-involvement digital purchasing contexts. Practically, the findings highlight the importance of risk reduction strategies, such as transaction security, product authentication, and transparent policies, in enhancing consumers’ purchase intention.